Treatment of Upper Limb Paresis With Repetitive Peripheral Nerve Sensory Stimulation and Motor Training: Study Protocol for a Randomized Controlled Trial - Conforto, Adriana B.; Machado, André G.; Menezes, Isabella; Ribeiro, Nathalia H. V.; Luccas, Rafael; Pires, Danielle S.; Leite, Claudia da Costa; Plow, Ela B.; Cohen, Leonardo G. (Frontiers in Neurology, 2020)
Background: Repetitive peripheral nerve sensory stimulation (RPSS) has emerged as a potential adjuvant strategy to motor training in stroke rehabilitation. The aim of this study is to test the hypothesis that 3-hour sessions of active RPSS associated with functional electrical stimulation (FES) and task-specific training (TST) distributed three times a week, over six weeks, is more beneficial to improve upper limb motor function than sham RPSS in addition to FES and TST, in subjects with moderate to severe hand motor impairments in the chronic phase (> 6 months) after stroke. Methods: In this single-center, randomized, placebo controlled, parallel-group, double-blind study we compare the effects of 18 sessions of active and sham RPSS as add-on interventions to FES and task-specific training of the paretic upper limb, in 40 subjects in the chronic phase after ischemic or hemorrhagic stroke. The primary outcome measure is the Wolf Motor Function Test (WMFT) after 6 weeks of treatment. The secondary outcomes are the WMFT at 3, 10 and 18 weeks after beginning of treatment, as well as the following outcomes measured at 3 weeks 6, 10 and 18 weeks: Motor Activity Log; active range of motion of wrist extension and flexion; grasp and pinch strength in the paretic and nonparetic sides (the order of testing is randomized within and across subjects); Modified Ashworth Scale; Fugl-Meyer Assessment-Upper Limb in the paretic arm; Barthel Index; Stroke Impact Scale. Discussion: This project represents a major step in developing a rehabilitation strategy with potential to have impact on the treatment of stroke patients with poor motor recovery in developing countries worldwide. The study preliminarily evaluates a straightforward, non-invasive, inexpensive intervention. If feasibility and preliminary efficacy are demonstrated, further investigations of the proposed intervention (underlying mechanisms/ effects in larger numbers of patients) should be performed. Ethics and Dissemination: The protocol, registered at clinicaltrials.gov, was approved by the institutional and the Brazilian federal ethics committees. Dissemination will include presentation in conferences, peer-reviewed publications, presentation to patients and public groups.